Evidence for Cognitive Deficits in X-Linked Charcot-Marie-Tooth Disease. (17th March 2020) - Kasselimis, Dimitrios; Karadima, Georgia; Angelopoulou, Georgia; Breza, Marianthi; Tsolakopoulos, Dimitrios; Potagas, Constantin; Panas, Marios; Koutsis, Georgios
Abstract: Objective: X-linked Charcot-Marie-Tooth disease (CMTX) is an hereditary neuropathy caused by mutations in GJB1 coding for connexin-32, found in Schwann cells, but also expressed in oligodendrocytes. Reports have identified CNS involvement in CMTX, but no systematic study of cognitive function has been published. Methods: We assessed 24 CMTX patients (13 males; 9 GJB1 mutations) with a comprehensive neuropsychological battery, including tests of memory, language, and executive functions. Results: No differences in cognitive performance were observed between males and females. A case-by-case investigation revealed selective deficits in individual patients. One subgroup (29%) demonstrated executive abnormalities; and a non-overlapping subgroup (29%), prominent reading (decoding) abnormalities. Conclusions: The present data provide evidence for cognitive deficits in CMTX. Emerging neuropsychological patterns are also discussed.